2018
DOI: 10.4236/ojem.2018.64012
|View full text |Cite
|
Sign up to set email alerts
|

On Hemostasis of Cold Atmospheric Air Plasma

Abstract: The efficacy and mechanism of a cold atmospheric-pressure air plasma (CAAP), which carries abundant atomic oxygen (OI), on blood coagulation are studied. The tests on sodium citrate mixed blood-droplet samples show that 1) The heat delivered by the CAAP has no impact on the observed clot formation, 2) Plasma effluent activates platelets to promote coagulation state and cascade, and 3) The degree of clotting increases with the OI flux delivered by the CAAP. The full clotting time is shortened from about 25 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In the following, two trials are presented. Two adult swines with blood pressure compatible to that of an adult human being, were used as animal models [38], and the similar trials were repeated on each swine. Each swine was first injected with calmative-stresnil and fastened on a table.…”
Section: Assay Via Animal Model To Demonstrate Caap Hemostasis Capacitymentioning
confidence: 99%
“…In the following, two trials are presented. Two adult swines with blood pressure compatible to that of an adult human being, were used as animal models [38], and the similar trials were repeated on each swine. Each swine was first injected with calmative-stresnil and fastened on a table.…”
Section: Assay Via Animal Model To Demonstrate Caap Hemostasis Capacitymentioning
confidence: 99%
“…It is reported that the first hour since injury is the “golden time” for rescue lives, and the initial 10 min (so-called platinum ten) is even more precious, during which time the bleeding should be fully controlled so as to ensure survival of the victims. 6 …”
Section: Introductionmentioning
confidence: 99%